Jogo de xadrez: o esporte da mente - Goussain, Blaha Gregory Correia dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This work presents an analysis of the practice of the game of chess in mathematics education, since the practice of this game brings countless benefits to the student's cognitive development in relation to mathematical logic, searching for adequate means through organization and planning to achieve a goal. This analysis was carried out by means of a qualitative bibliographical research based on bibliographical sources, developed based on books and scientific articles, with the purpose of consulting and studying the ways in which the game of chess is implemented in the school unit as an instrument pedagogical. It was observed that chess is an alternative pedagogical strategy for the teaching of mathematics, being observed, in the analyzed works, the better performance of these students, in aspects such as logical reasoning, concentration, memory, patience, planning, self-confidence and imagination. Therefore, according to the researches, students are able to carry out their activities with significant improvement in their mental and practical development. Therefore, it is possible to practice, as a pedagogical tool, the chess game in the classroom

Este trabalho traz uma análise sobre a prática do jogo de xadrez na educação matemática, visto que a sua prática pode contribuir para o desenvolvimento cognitivo do aluno em relação a lógica matemática, e na busca de meios adequados e planejamento para alcançar um objetivo. Tal análise foi realizada por meio de uma pesquisa bibliográfica, de natureza qualitativa, a partir de fontes bibliográficas, desenvolvida com base em livros e artigos científicos, com os objetivos de consultar e estudar as maneiras de implantação do jogo de xadrez na unidade escolar como instrumento pedagógico. Observou-se que o xadrez se configura como uma estratégia pedagógica alternativa para o ensino da matemática, sendo observado, nos trabalhos analisados, melhor rendimento destes alunos, nos aspectos como raciocínio lógico, concentração, memória, paciência, planejamento, autoconfiança e imaginação. Portanto, de acordo com os trabalhos pesquisados, os alunos são capazes de realizar suas atividades com melhora significativa em seu desenvolvimento mental e prático. Logo é possível praticar, como ferramenta pedagógica, o jogo de xadrez em sala de aula
Keywords: Xadrez; Matemática - Estudo e ensino; Jogos de estratégia (Matemática); Chess